KEBERADAAN DAN PERANAN PARTAI POLITIK DI NEGARA DEMOKRASI (DI INDONESIA) - Deden Haria Garmana (LPPM UNSAP & FISIP UNSAP, 2020)
The role of political parties greatly influences the condition and future of the nation, because through the results of these elections, a new leadership will be elected through general elections. The meaning of democratization in the life of the nation and the state is one of them by holding general elections which will lead a nation to a new leadership and government, with the hope that the new government will improve life in all fields. Thus, the change in the direction of the nation's and state's policies is inseparable from the role of political parties that fill the people's democratic party with a number of party visions and missions that vary according to their ideology.